Application of a novel lytic Jerseyvirus phage LPSent1 for the biological control of the multidrug-resistant Salmonella Enteritidis in foods - Al-Hindi, Rashad R.; Alharbi, Mona G.; Alotibi, Ibrahim; Azhari, Sheren A.; Algothmi, Khloud M.; Esmael, Ahmed (Frontiers in Microbiology, 2023)
Non-typhoidal Salmonella is the tremendously predominant source of acquired foodborne infection in humans, causing salmonellosis which is a global threat to the healthcare system. This threat is even worse when it is combined with the incidence of multidrug-resistant Salmonella strains. Bacteriophage therapy has been proposed as a promising potential candidate to control a diversity of foodborne infective bacteria. The objective of this study designed to isolate and characterize lytic phages infecting zoonotic multi-drug resistant and strong biofilm producer Salmonella enterica serovar Enteritidis EG.SmE1 and then apply the isolated phage/s as a biocontrol agent against infections in ready-to-eat food articles including milk, water, apple juice, and chicken breasts. One lytic phage (LPSent1) was selected based on its robust and stable lytic activity. Phage LPSent1 belonged to the genus Jerseyvirus within the Jerseyvirinae subfamily. The lysis time of phage LPSent1 was 60 min with a latent period of 30 min and each infected cell burst about 112 plaque-forming units. Phage LPSent1 showed a narrow host range. Furthermore, the LPSent1 genome did not encode any virulence or lysogenic genes. In addition, phage LPSent1 had wide pH tolerance, prolonged thermal stability, and was stable in food articles lacking its susceptible host for 48 h. In vitro applications of phage LPSent1 inhibited free planktonic cells and biofilms of Salmonella Enteritidis EG.SmE1 with a lower occurrence to form phage-resistant bacterial mutants which suggests promising applications on food articles. Application of phage LPSent1 at multiplicities of infections of 100 or 1000 showed significant inhibition in the bacterial count of Salmonella Enteritidis EG.SmE1 by 5 log10/sample in milk, water, apple juice, and chicken breasts at either 4°C or 25°C. Accordingly, taken together these findings establish phage LPSent1 as an effective, promising candidate for the biocontrol of MDR Salmonella Enteritidis in ready-to-eat food.